2020
DOI: 10.1186/s40814-020-00642-w
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study comparing internal fixation for undisplaced versus hip arthroplasty for displaced femoral neck fracture in the elderly: a pilot study for a clinical trial

Abstract: Introduction: The literature regarding undisplaced femoral neck fractures (FNF) is sparse. The aim of this prospective feasibility study is to compare the clinical outcome after undisplaced FNF treated with internal fixation (IF) and displaced FNF treated with hip arthroplasty. We hypothesized that hip arthroplasty would give a lower incidence of reoperations. Methods: A total of 235 patients were included with a median age of 84 years (range 65-99). A consecutive series of 65 patients with undisplaced FNF wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…This could lead to surgical bias, as a surgeon might be more prone to choose an IF for a 72-year-old patient with a 20-degree posterior tilt compared with an 82-year-old patient. This could explain some of the baseline difference, which, however, could also be due to an underlying confounding in the population sustaining a displaced or undisplaced FNF, but previous studies have not found a major difference between groups (Mukka et al 2020, Richards et al 2020. There is, however, no difference in the 1-year mortality between hemiarthroplasty and IF despite the baseline difference.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This could lead to surgical bias, as a surgeon might be more prone to choose an IF for a 72-year-old patient with a 20-degree posterior tilt compared with an 82-year-old patient. This could explain some of the baseline difference, which, however, could also be due to an underlying confounding in the population sustaining a displaced or undisplaced FNF, but previous studies have not found a major difference between groups (Mukka et al 2020, Richards et al 2020. There is, however, no difference in the 1-year mortality between hemiarthroplasty and IF despite the baseline difference.…”
Section: Discussionmentioning
confidence: 88%
“…This could explain some of the baseline difference, which, however, could also be due to an underlying confounding in the population sustaining a displaced or undisplaced FNF, but previous studies have not found a major difference between groups (Mukka et al. 2020 , Richards et al. 2020 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The sample size ranged from 17 to 417 participants. Three studies reported solely on pediatric populations [ 16 , 17 , 18 ], while nine studies included only participants above 50 years of age [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The studies included those that reported the use of both closed and open fracture-reduction techniques and employed a wide range of implants, most commonly cannulated screws (28 studies).…”
Section: Resultsmentioning
confidence: 99%